Probing the electromagnetic field of a 15-nanometre hotspot by single molecule imaging - Cang, Hu; Labno, Anna; Lu, Changgui; Yin, Xiaobo; Liu, Ming; Gladden, Christopher; Liu, Yongmin; Zhang, Xiang (Nature (London), 2011)
Mapping electromagnetic hotspots It is well known that hotspots can appear on rough metallic surfaces exposed to light, where the incident light is concentrated on the nanometre scale to produce an intense electromagnetic field. This 'surface enhancement' effect can be used, for example, to detect molecules, because weak fluorescence signals are strongly enhanced by the hotspots. Such hotspots are associated with localized electromagnetic modes, caused by the randomness of the surface texture, but the detailed profile of the local electromagnetic field is so far unknown. Cang et al . now describe an ingenious experiment that exploits the Brownian motion of single molecules to probe the local field. They succeed in imaging the fluorescence enhancement profile of single hotspots on the surface of aluminium thin-film and silver nanoparticle clusters with accuracy down to 1 nm, and find that the field distribution in a hotspot follows an exponential decay. On rough metallic surfaces hotspots appear under optical illumination that concentrate light to tens of nanometres. This effect can be used to detect molecules, as weak fluorescence signals are strongly enhanced by the hotspots. Such hotspots are associated with localized electromagnetic modes, caused by the randomness of the surface texture, but the detailed profile of the local electromagnetic field is unknown. Here, an ingenious approach is described, making use of the Brownian motion of single molecules to probe the local field. The study succeeds in imaging the fluorescence enhancement profile of single hotspots on the surface of aluminium thin-film and silver nanoparticle clusters with accuracy down to one nanometre, and finds that the field distribution in a hotspot follows an exponential decay. When light illuminates a rough metallic surface, hotspots can appear, where the light is concentrated on the nanometre scale, producing an intense electromagnetic field. This phenomenon, called the surface enhancement effect 1 , 2 , has a broad range of potential applications, such as the detection of weak chemical signals. Hotspots are believed to be associated with localized electromagnetic modes 3 , 4 , caused by the randomness of the surface texture. Probing the electromagnetic field of the hotspots would offer much insight towards uncovering the mechanism generating the enhancement; however, it requires a spatial resolution of 1–2 nm, which has been a long-standing challenge in optics. The resolution of an optical microscope is limited to about half the wavelength of the incident light, approximately 200–300 nm. Although current state-of-the-art techniques, including near-field scanning optical microscopy 5 , electron energy-loss spectroscopy 6 , cathode luminescence imaging 7 and two-photon photoemission imaging 8 have subwavelength resolution, they either introduce a non-negligible amount of perturbation, complicating interpretation of the data, or operate only in a vacuum. As a result, after more than 30 years since the discovery of the surface enhancement effect 9 , 10 , 11 , how the local field is distributed remains unknown. Here we present a technique that uses Brownian motion of single molecules to probe the local field. It enables two-dimensional imaging of the fluorescence enhancement profile of single hotspots on the surfaces of aluminium thin films and silver nanoparticle clusters, with accuracy down to 1.2 nm. Strong fluorescence enhancements, up to 54 and 136 times respectively, are observed in those two systems. This strong enhancement indicates that the local field, which decays exponentially from the peak of a hotspot, dominates the fluorescence enhancement profile.